Determinants of the Performance of Health Workers in the Tampan Mental Hospital of Riau Province in 2022 - Rini Eka Putri; Yessi Harnani; Budi Hartono; Hetty Ismainar; Irana Oktavia (Budapest International Research and Critics University, 2022)
The research objective is to analyze determinants of the performance of health workers in the Tampan Mental Hospital of Riau Province in 2022. This type of research is quantitative analytic with a cross sectional study design. This research is conducted at the Tampan Mental Hospital in Riau Province which is carried out from April 2022-June 2022. The population in this study are all employees of the health workforce at the Tampan Mental Hospital, Riau Province, totaling 265 people consisting of 7 mental specialists, 25 general practitioners, 6 dentists, 6 psychologists, 167 nurses, 4 pharmacists, diploma 3 Pharmacy 8 people, diploma 3 analysis 3 people, radiology 3 people, medical records 17 people, nutrition 7 people, 2 speech therapists, 2 occupational therapy, and physiotherapy 8 people. This study used bivariate analysis. The results of the study which consist of ability and skill, tenure, leadership, reward, incentive, organizational structure, motivation, job satisfaction, workload, show that only reward, incentive, and workload are related to the performance of health workers in the Tampan Mental Hospital of Riau Province in 2022.